Isokinetic Testing: Why it is More Important Today than Ever - Kevin E Wilk; Christopher A Arrigo; George J Davies (International Journal of Sports Physical Therapy)
Isokinetics is a proven method to train and objectively assess the capability of muscle groups, particularly at the knee. The current re-injury rates and less than optimal return to sport percentages seen following anterior cruciate ligament surgery highlights the need for greater focus on what tests and methods are used to make these critical decisions. Isokinetics remains the best single method to objectively determine dynamic muscle strength, power, rate of force development and endurance. These factors make it well-suited to play a crucial role in influencing the appropriate patient progression through a rehabilitation program and assisting in determining return to play readiness following injury or surgery. In this article we will discuss why we believe isokinetics is a useful and necessary testing method, and elucidate testing parameters and goals used during knee extension/flexion assessment.